Cabuya (Furcraea andina, Asparagaceae): a biocultural persistence for the reproduction of the Puruhá social being in the Guano River microbasin (Ecuadorian Andes) - Aguirre Merino, Christian Paúl; Jarrín Zambrano, Ginno Sidney; Guilcapi Pacheco, Edmundo Danilo; Montenegro Ocaña, Fabián Ramón (Instituto de Ecología, A.C., 2023)
Background and Aims: The Central Andes of Ecuador have been the scene of the cultural development of the indigenous Puruhá ethnic group. This development has been linked to the presence of the cabuya from the socio-ecological appropriation of its landscape (cabuyales) to its xeric ecosystems of the thorny steppe. Previous investigations had shown a multiplicity of uses of cabuya in the Puruhá ethnic group, but had not focused on the analysis of the biocultural persistence of this plant for the reproduction of its social being (relationships, practices and socio-ecological patterns that are produced and reproduced for the existence and survival of a particular ethnic group). Therefore, the objective of the study was to register the indicators of the cabuya as a key ethnospecies. Methods: A total of 107 field trips were carried out for the application of participatory methodologies such as participant observation and the interview in the Kichwa language. A total of 135 indigenous people were interviewed on various occasions (Max.=94/ x̅=68/Min.=32; 121 women and 14 men). The historical uses were documented through the bibliographic review of specialized literature. Key results: A total of 50 ethnobotanical uses associated with the current and historical contexts of the Puruhá culture were recorded, all these valued highly from the functions of the psycho-socio-cultural structure between 86% and 93%. The ethnotaxonomy recorded a diversity of 11 vernacular names associated with the ethnobotanical uses of cabuya, while the irreplaceability was recorded from the pre-Hispanic period of Integration (800 AD-1534 AD) to the present (XXI century). Conclusions: The results confirm that the technological process involved in the manufacture and socio-ecological use of biocultural artifacts of Furcraea andina visibilizes a routinization in the habitual activities of the puruháes and a cultural identity persistence of around 1200 years that has continuously enabled reproduction of the Puruhá social being.